Perancangan Sistem Informasi Anime Berbasis Web Menggunakan Wordpress - Sahri, Samsul; , Heru Supriyono, ST. MSc. PhD (2017)
Anime is a term to categorize media animation originating from Japan, have specific characteristics in terms of the depiction of the story, characters, and backgrounds with colorful that can be enjoyed by different types of audiences. Anime grow along with the advancement of technology, with the story of an increasingly diverse and varied. With the development of the Internet, serving anime began circulating widely through various media, especially in the online media. The purpose of this research is to create anime information website is still difficult to obtain. Information system design utilizes WordPress as the media in the creation of websites. Making the website will focus on information related to anime title, plot, characters, and related information with illustrations or visual media as supporting information with data collection methods. Results obtained in the form of a website that contains information from various anime that aired and spread through the Internet, which can be accessed easily.